Efficient data detection algorithms in single- and multi-carrier systems without the necessity of a guard period - Sinn, Christian Vincent; Gotze, Jurgen; Haardt, Martin (2002 IEEE International Conference on Acoustics, Speech, and Signal Processing, 2002)
To enable efficient detection strategies in wireless communications a guard period is frequently inserted into the transmitted data symbols. This is the case in OFDM systems and in single-carrier systems with frequency domain equalization. Especially for transmissions over wireless channels with long delay spreads the required guard period is quite long. Here we present efficient data detection algorithms that are applicable if a guard period is not inserted after every symbol or if it is omitted completely. The increase of the computational requirements in the base station is moderate and can be implemented via parallel processing. Finally, an OFDM system without guard periods is presented as an example.